An Investigation on the Influence of Various Biochemical Tenderness Factors on Eight Different Bovine Muscles - Amelia Welter; Colin Chun; Erika Geisbrecht; Geraldine Magnin-Bissel; Michael Chao; Peang Hammond; Travis O'Quinn; Wan Jun Wu (Meat and Muscle Biology, 2022)
This study’s objective was to understand the relationships between biochemical tenderness components andobjective/sensory measure of tenderness of 8 muscles from beef carcasses. Longissimus thoracis (LT), pectoralis profundus (PP), supraspinatus, triceps brachii (TB), gluteus medius (GM), rectus abdominus (RA), rectus femoris, and semitendinosus (ST) were collected from 10 USDA upper 2/3 Choice beef carcasses and assigned to a 2- or 21-d aging period (n=160). Troponin-T degradation, desmin degradation, sarcomere length, collagen content, mature collagen crosslink density, intramuscular lipid content, pH, Warner-Bratzler Shear Force (WBSF), and trained sensory panel analyses were measured. A Pearson correlation analysis was conducted to determine the relationship between each tenderness contributor measured in this study with WBSF or the overall tenderness evaluated by the trained panelist for each of the 8 muscles.In addition, multivariate regression models were constructed to confirm this relationship. The results showed that muscle anatomical locations and physiological functions driven by muscle fiber types may explain some of the biochemical/tenderness differences found in this study. The correlation analysis showed that each muscle had a specific tenderness factor(s)that contributed to the overall tenderness. For instance, tenderness for LT, TB, GM, RA, and ST may be influenced more by proteolytic degradation, while the collagen characteristics may primarily influence tenderness for PP. Also, lipid content has a significant influence on GM tenderness. Finally, the multivariate regression model showed that almost all of the biochemical measurements conducted in this study contributed to overall tenderness to some degree across muscles.Increasing the knowledge base on the various tenderness components’ level of contribution will allow end-users to develop specific tenderness management strategies to ensure consistent tenderness in beef products.